The Effect of Work Stress and Work Conflict on Employees Turnover Intention In Middle Small Micro Enterprises (MSMEs) In South Tangerang Region - Nurjaya Nurjaya; Heri Erlangga; Lim Zhen Hong; Kiki Dwi Wijayanti (Har Press Indonesia, 2020)
This study aims to determine the effect of work stress and work conflict on the turnover intention of employees of Micro, Small and Medium Enterprises (MSMEs) in the South Tangerang Region. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study work stress have a significant effect on the turnover intention by 37.0%, the hypothesis test is obtained t count> t table or (7,438> 1,986). Work conflict has a significant effect on the turnover intention by 49.9%, hypothesis testing is obtained t count> t table or (9.679> 1.986). Work stress and work conflict simultaneously have a significant effect on turnover intention with the regression equation Y = 9.021 + 0.272X1 + 0.510X2. The contribution of the effect was 55.2%, the hypothesis test obtained F count> F table or (57.286> 2,700).